The Evaluation of Maxillary Sinus Dimensions in Different Craniofacial Patterns: A Systematic Review and Meta-Analysis - Ramyaja Chunduru; Pamila Rachel; Vignesh Kailasam; Sridevi Padmanabhan (Galenos Yayinevi, 2023)
This systematic review was intended to evaluate the maxillary sinus dimensions in vertical and sagittal craniofacial patterns and to assess if there was a difference among the craniofacial patterns. A systematic search was performed in seven databases till February 2021. The risk of bias was performed with modified Newcastle Ottawa scale. Meta-analysis was performed using random effects model. Twelve studies were included in the review and 8 in the meta-analysis. Compared to Class I malocclusion, the maxillary sinus area is greater in Class II and lesser in Class III malocclusion. On comparing normo-divergent growth pattern, the maxillary sinus area is lesser in hypo-divergent and greater in hyper-divergent individuals. Most of the studies were graded as satisfactory. The measurements are greater in hyper-divergent Class II malocclusion and in males.